Фискальные взаимоотношения в ЕС: теоретические аспекты, современное состояние и перспективы - Кулай, Алина Васильевна; Kulaj, A. V. (УО «Полесский государственный университет», 2016)
Были выявлены методологическая основа сущности межбюджетных отношений в ЕС, а также научные и теоретические аспекты межбюджетных отношений на национальном уровне. Были охарактеризованы специфика и особенности субсидиарности на основе немецкого кооперативного федерализма. Были выделены структура доходов в бюджет ЕС и налоговая нагрузка на бюджеты стран-членов. The methodological foundation of the fiscal relations essence in the EU, as well as scientific and theoretical aspects of interbudgetary relations at the national level were revealed. The specificity and peculiarities of the subsidiarity-based German cooperative federalism were characterized. The fiscal relations basis in the EU is that of flexible distribution of authority and resources between the central federal institutions and administrative territorial units. The nature and fundamentals of the budget policy at supranational level, structure of incomes to the EU budget and the tax load on the member countries budgets were discerned. Analyzing fiscal relations in the EU, the integrated approach that combines the member countries and the EU budget relations with revenues and allocations was applied
Fiscal relations in EU: theoretical aspects, current status and prospects
Keywords: фискальные взаимоотношения национальных бюджетов стран-членов ЕС; бюджет ЕС